23例套细胞淋巴瘤患者临床特征及预后相关因素分析 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To investigate the clinical characteristics and prognostic factors of mantle cell lymphoma (MCL) patients. METHODS: The clinical data of 23 MCL patients were retrospectively analyzed. Immunohistochemical stain was performed to detect the protein expressions of Mcl-1, pNF-κB p65 and 14-3-3ζ of MCL patients to analyze its prognostic factors. RESULTS: Among 23 MCL patients, there were 17(73.9%) patients with IPI 0–2 (low risk group) and 6(26.1%) patients with IPI 3–4. Only the rate of 2y-progression-free survival (PFS) of group IPI 0–2 was superior to that of group IPI 3–4 patients (47.1% vs 0, P=0.049); There were 16 (69.5%) patients with MIPI < 5.7, whose rates of overall response rate (ORR), 2y overall survival (OS) and PFS were better than those of the ones with MIPI ≥ 5.7(ORR: 81.3% vs 33.3% P=0.032; OS: 68.8% vs 16.7% P=0.041; PFS: 50% vs 0, P=0.040 respectively). The rates of ORR, 2y-OS and 2y-PFS (100.0%, 80.0% and 70.0%) of patienets received regimen R+CHOP(E) were all superior to those (38.5%, 30.8% and 7.7%) of ones received regimen CHOP(E) (P=0.002, P= 0.024, P=0.003, respectively). Among 12 patients, 2 out of 6 cases with Mcl-1 positive expression achieved good response (CR+PR) and 2y-OS, 1 case 2y-PFS; All 6 cases with Mcl-1 negative expression achieved good response (CR+PR) and 2y-OS, 5 cases 2y-PFS. 3 out of 6 cases with pNF-κB p65 positive expression achieved good response (CR+PR) and 2y-OS, 1 case 2y-PFS; 5 out of 6 cases with pNF-κB p65 negative expression achieved good response (CR+ PR) and 2y-OS/PFS. 5 out of 8 cases with 14-3-3ζ positive expression achieved good response (CR+PR), 4 cases 2y-OS, and 3 cases 2y-PFS. 3 out of 4 cases with 14-3-3ζ negative expression achieved CR, 4 cases 2y-OS, and 3 cases 2y-PFS. CONCLUSION: MCL patients had high heterogeneity. MIPI has better prognostic significance than IPI. R+CHOP(E) as first line treatment improved the rates of OS/PFS. The expressions of Mcl-1, pNF-κB p65 and 14-3-3ζ proteins in MCL might be related to prognosis.